Assessment of Human Health Risk Indices Due to Metal Contamination in the Surface Water of the Negro River Sub-Basin, Áncash - Walter Bravo-Zevallos (2024)
The accelerated loss of glacial cover in the Cordillera Blanca in Áncash, Peru, exposes the underlying rocks with high concentrations of sulfides from the Chicama Formation to oxidation and leaching processes, generating acid rock drainage (ARD) in glacial and periglacial areas. These are transported by surface runoff, contaminating the surface water with high concentrations of metals and sulfates, as well as increasing the acidity, which poses a risk to human health and the ecosystem. Therefore, the risk indices for human health due to metal contamination were evaluated at 19 surface water sampling points distributed in the Río Negro sub-basin. Hydrochemical analyses revealed average metal concentrations in the following order: Fe (28.597 mg/L), Al (3.832 mg/L), Mn (1.085 mg/L), Zn (0.234 mg/L), Ni (0.085 mg/L), Co (0.053 mg/L), Li (0.036 mg/L), Cu (0.005 mg/L), and Pb (0.002 mg/L). The risk was determined by calculating the Heavy Metal Pollution Index (HPI) and the Hazard Index (HI). The average HPI value was 360.959, indicating a high level of contamination (HPI ≥ 150). The human health risk assessment indicated that adverse effects caused by iron, lithium, and cobalt in children and adults should be considered. Through the use of Pearson correlation analysis, principal component analysis, and cluster analysis, it was identified that SO42−, Fe, S, Al, Co, Mn, Ni, Zn, and Li originate from natural sources, associated with the generation of ARD in glacial and periglacial areas.